2021
DOI: 10.3390/jpm11060520
|View full text |Cite
|
Sign up to set email alerts
|

IL17F: A Possible Risk Marker for Spondyloarthritis in HLA-B*27 Negative Brazilian Patients

Abstract: HLA-B*27 is an important marker for spondyloarthritis (SpA), however, many SpA patients are HLA-B*27 negative. Thus, the aim of this study was to investigate the influence of IL17, TNF and VDR gene polymorphisms in SpA patients who were HLA-B*27 negative. This case-control study was conducted in 158 patients [102 patients with ankylosing spondylitis (AS) and 56 with psoriatic arthritis (PsA)] and 184 controls. HLA-B*27 genotyping was performed using PCR-SSP and IL17A (rs2275913), IL17F (rs763780), TNF-308 (rs1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…validated that the T allele of rs1799724 was associated with susceptibility to AS independently of HLA-B27 ; nevertheless, the genotype distribution of rs1799724 deviated from HWE in the control group ( 44 ). A study in Brazilian population with HLA-B27 negativity found no association between two SNPs (rs1800629 and rs361525) in TNFα and AS ( 45 ). In the present study, all the interested SNPs obeyed HWE and no association between the SNPs and the risk of AS was observed in HLA-B27 positive or negative individuals.…”
Section: Discussionmentioning
confidence: 99%
“…validated that the T allele of rs1799724 was associated with susceptibility to AS independently of HLA-B27 ; nevertheless, the genotype distribution of rs1799724 deviated from HWE in the control group ( 44 ). A study in Brazilian population with HLA-B27 negativity found no association between two SNPs (rs1800629 and rs361525) in TNFα and AS ( 45 ). In the present study, all the interested SNPs obeyed HWE and no association between the SNPs and the risk of AS was observed in HLA-B27 positive or negative individuals.…”
Section: Discussionmentioning
confidence: 99%
“…This statement aligns with several recent studies that have provided evidence for the involvement of vitamin D in AS via influencing both the adaptive and innate immune systems, rather than only affecting calcium metabolism. These findings suggest the potential benefits of supplemental vitamin D for individuals with this particular condition [ 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of HLAB-27 in AS sufferers was found to be 66% in this research. The observed disparity might perhaps be ascribed to the racial genetic variability within the groups under investigation [ 19 ]. The findings may validate the pursuit of novel diagnostic markers for AS that provide improved accuracy.…”
Section: Discussionmentioning
confidence: 99%
“…[21] IL-17A and IL-17F are 2 important members in the IL-17 family, they share up to 60% structure homology and induce the production of inflammatory mediators. [21] To date, the SNPs in the IL17 gene have been reported to be associated with an increased risk for different autoimmune diseases including RA, [22,23] AS, [24,25] spondyloarthritis, [26] inflammatory bowel disease [27] and adult SLE. [28,29] However, few studies were performed to investigate the role of IL17 SNPs in JIA and JSLE in a Chinese population.…”
Section: Introductionmentioning
confidence: 99%